2001
DOI: 10.1203/00006450-200109000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Salbutamol Pressurized Metered-Dose Inhaler Administered Via Small-Volume Spacer Devices in Intubated, Spontaneously Breathing Rabbits

Abstract: Little is known about the ability of small-volume valved spacer devices to deliver a significant amount of an aerosolized drug to the lungs of babies. This study compared the in vitro delivery of salbutamol administered via Aerochamber-Infant (145 mL), Babyhaler (350 mL), and metallic NES-spacer (250 mL), as well as the in vivo delivery using an animal model. The lung deposition study of technetium-99m-labeled salbutamol was conducted in six anesthetized, intubated (3.0-mm endotracheal tube simulating orophary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…We think that these three elements are responsible for the superior performance of the device. These data are in agreement with those of Dubus et al, who compared albuterol delivery via pMDI in spontaneously breathing rabbits intubated with an ETT with an ID = 3 mm. They found that the valved holding chamber made of non‐electrostatic material was the most efficient one.…”
Section: Discussionsupporting
confidence: 92%
“…We think that these three elements are responsible for the superior performance of the device. These data are in agreement with those of Dubus et al, who compared albuterol delivery via pMDI in spontaneously breathing rabbits intubated with an ETT with an ID = 3 mm. They found that the valved holding chamber made of non‐electrostatic material was the most efficient one.…”
Section: Discussionsupporting
confidence: 92%
“…In a model of anesthetized rabbits that were intubated with a 3.0-mm ETT, deposition of an aerosol administered via a spacer placed on the ventilator's inspiratory line or directly into the ETT ranged from 0.2 to 0.4% of the emitted dose (6,7). In conditions of uncontrolled ventilation in nonparalyzed rabbits, deposition reached a maximum of 5% of the emitted dose (7,9). The use of a jet nebulizer resulted in Ͻ1% of the charge deposited into the lungs of rabbits with a 3.5-mm ETT (4,5,8).…”
mentioning
confidence: 99%
“…For example, in vivo studies on rats are common and different models were developed especially for BPD studies 25 . Other in vivo animal models exist, such as baboon 26 , macaque 27 , piglet 28 or rabbit 29 , and could be used as infant-like model for aerosol regional deposition studies. However, using animal models is expensive and time-consuming ( i .…”
Section: Introductionmentioning
confidence: 99%